A new xanthone and a new benzophenone from the roots of Garcinia hombroniana - Wan Salleh, Wan Mohd Nuzul Hakimi; On, Shamsul; Ahmad, Farediah; Mohd Sirat, Hasnah; Bakhtiar, M. Taher; Sarker, Satyajit Dey; Nahar, Lutfun (Elsevier Ltd, 2020)
In this study, the roots of Garcinia hombroniana were chemically investigated, in which novel derivatives of xanthone and benzophenone, known as garcihomxanthone (1) and garcihombrianone (2), respectively, together with garceduxanthone (3), cheffouxanthone (4), norathyriol (5), and 2,3′,4,5′-tetrahydroxy-6-methox- ybenzophenone (6) were isolated.. The structures of these compounds were elucidated by extensive spectro- scopic techniques and evaluated based on references with previous literature data